KAJIAN BANGUNAN PELINDUNG PANTAI DARI BAHAYA ABRASI/EROSI DENGAN MENGGUNAKAN BREAKWATER DI INDONESIA - Daniel Jaya (Jurnal Informasi, Perkebunan dan Sipil, 2023)
This study aims to find out how important the breakwater is so that in future planning it will be better, especially in Indonesia so that the level of abrasion/erosion that occurs can be reduced. It is known that the level of coastal erosion in Indonesia is very high, therefore further studies need to be carried out. This study uses a literature study as a way of collecting data. Various methods have been used by researchers to reduce the level of coastal erosion in Indonesia. These methods should be able to help policy makers in Indonesia choose wisely to plan coastal protection structures. Technical support and appropriate policies in the use of breakwaters are urgently needed to minimize the dangers of coastal abrasion/erosion in Indonesia.